Los efectos jurídicos del decreto 1227 de 2015 para la pensión de vejez (2017)
The Constitutional Court, through sentence T-063/15, protected the fundamental rights to human dignity, to the sexual identity and legal personality, which it considered violated before the refusal of a Notary of Medellín to authorize the change of the sex registered in the civil registry of birth and other identity documents, without having to resort to a process of voluntary jurisdiction. As a consequence of this ruling was issued Decree 1227 of 2015 that defined the procedure to make effective the change of sex in the citizenship card for the trans people. The ruling and the issuance of the aforementioned decree have a scope in specific aspects but not for access to benefits in the General Pension System. In spite of this, in agreement with the constitutional precedent it is understood that the protection by the Constitutional Court to the Trans people is not reduced to the modification of the sex...